2010
DOI: 10.1128/jvi.01545-09
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Molecular Mechanism of Dual Resistance to Nucleoside and Nonnucleoside Reverse Transcriptase Inhibitors

Abstract: Recently, mutations in the connection subdomain (CN) and RNase H domain of HIV-1 reverse transcriptase (RT) were observed to exhibit dual resistance to nucleoside and nonnucleoside reverse transcriptase inhibitors (NRTIs and NNRTIs). To elucidate the mechanism by which CN and RH mutations confer resistance to NNRTIs, we hypothesized that these mutations reduce RNase H cleavage and provide more time for the NNRTI to dissociate from the RT, resulting in the resumption of DNA synthesis and enhanced NNRTI resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 59 publications
1
49
0
Order By: Relevance
“…In addition, some NNRTI resistance mutations are associated with impaired RNase H activity (69,(71)(72)(73)(74)(75), and N348I has been shown to reduce the rate of RNA template degradation (8,10,24,76). Furthermore, reduced RNase H activity may be associated with enhanced NNRTI resistance (77). To investigate the impact of N348I or M184V/N348I on the RNase H activity of E138K-containing RT, we monitored multicycle RNase H-mediated RNA cleavage in time course experiments using WT RT and the E138K, E138K/M184V, and E138K/ M184V/N348I RT variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some NNRTI resistance mutations are associated with impaired RNase H activity (69,(71)(72)(73)(74)(75), and N348I has been shown to reduce the rate of RNA template degradation (8,10,24,76). Furthermore, reduced RNase H activity may be associated with enhanced NNRTI resistance (77). To investigate the impact of N348I or M184V/N348I on the RNase H activity of E138K-containing RT, we monitored multicycle RNase H-mediated RNA cleavage in time course experiments using WT RT and the E138K, E138K/M184V, and E138K/ M184V/N348I RT variants.…”
Section: Resultsmentioning
confidence: 99%
“…Transit-kinetic analysis has shown that E138K resistance to RPV is due mainly to an enhanced dissociation rate of RPV (11). N348I also confers resistance to NVP through decreased binding affinity (8) while inhibiting RNase H activity (10,77,99). Further biochemical and structural analyses may lead to the design of better NNRTIs with improved resistance profiles and potency.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes may not significantly alter the K d-DNA but could affect proper alignment of DNA with dNTP substrates or stability of the catalytic complex. The enhanced processivity of N348I RT may also contribute to NRTI resistance as it is possible that this property could provide more opportunities for unblocking chainterminated primers or NNRTI dissociation (38,39). The molecular details of these effects are not yet fully understood and should be addressed by structural studies of N348I RT.…”
Section: Discussionmentioning
confidence: 99%
“…Less clear is the role of RNase H in NVP resistance. Nikolenko et al (38) proposed that the decrease in RNase H activity of CSMs preserves the RNA template and provides more time for NNRTIs to dissociate from the RT, resulting in the resumption of DNA synthesis and FIGURE 9. A, superposition of molecular models of WT RT (multicolored schematic; see below) and p66 N348I / p51 N348I RT (magenta schematic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation